ANALISIS RASIO AKTIVITAS DAN PROFITABILITAS PADA PT. PELINDO IV (PERSERO) CABANG SAMARINDA TAHUN 2013 - 2017 - Silitonga, Ruben Winter (EKONOMIA, 2019)
Ruben Winter Silitonga, Activity and Profitability Analysis at PT. Pelindo IV (Persero) Samarinda Branch 2013 - 2017, under the guidance of Mr. Robin Jonathan and Mr. Murfat Effendi.Formulation of the problem whether the level of activity and profitability level of PT. Pelindo IV (Persero) Samarinda Branch in 2013 - 2017 in terms of activity ratio and profitability ratio, experienced growth.This research was conducted at PT. Pelindo IV (Persero) Samarinda Branch. Data sources include secondary data. Data collection technique use interviews with related parties and observations.The basic theory used in this study is financial management. While the analysis tool uses two ratios; activity ratios are total assets turnover ratio, fixed assets turnover ratio and working capital turnover, profitability ratios are net profit ratios margin, return on investment and return on equity.Based on the calculation of total assets turnover, it decreased in 2017 compared to 2013, seen from fixed asset turn over has decreased in 2017 compared to 2013, seen from the working capital turnover ratio experienced growth in 2017 compared to 2013. Then the net profit margin ratio decreased in 2017 compared to 2013, seen from the return on investment experienced a decline in 2017 compared to 2013 and the ratio of return on equity decreased in 2017 compared to 2013.It was concluded that the total assets turnover and fixed asset turnoverÂ overall decreased, this is due to the growth in total asset turnover and fixed assets turnover in the final year (in 2017) lower than the base year (in 2013), while overall working capital turnover experienced growth, This is due to the higher working capital turnover in the end of 2017 compared to the base year in 2013. For the overall profitability ratio has decreased, This is due to the turnover of the net profit margin ratio, return on investment, and return on equity in the final year (2017) lower than the base year (in 2013).Â